Changes in Sporulation, Packed Cell Volume, Malondialdehyde Level, Fecal Oocyst Count and Histopathology of Eimeria tenella-infected Broilers Treated with Pineapple (Ananas comosus) Crude Extracts - Juasook , A.; Aengwanich, W.; Chalalai, T.; Watwiengkam, N.; Asawapattanakul, T.; Promsud, W. (International Journal of Poultry Science, 2017)
Objective: This experiment was conducted to study the effects of pineapple (Ananas comosus) peel and core extracts for controlling in vitro and in vivo chicken cecal coccidiosis. Materials and Methods: In vitro, 5,000 unsporulated oocysts per well with three replicates were divided into 4 groups: incubated in distilled water, toltrazuril, pineapple peel and core extract, respectively, at 25°C for 48 h. The number of sporulated oocysts was counted using McMaster chamber method. In vivo, 100 heads of one-day-old male broilers were divided into 5 groups: control, infected with E. tenella oocysts, infected and treated with toltrazuril, infected and treated with pineapple peel extract and infected and treated with pineapple core extract. All infected groups were inoculated with 20,000 sporulated E. tenella oocysts at day 21 of the experiment. After 7 days of infection, all of the chicks were euthanized and the blood, feces and cecum were collected for analysis. Results: In vitro results showed that the number of sporulated E. tenella oocysts in the pineapple peel and core extract groups decreased significantly (p<0.05). Correspondingly, histopathological study of the cecum showed that infection of E. tenella was greatly decreased in these groups. Surprisingly, pineapple extract groups had a significant increase in malondialdehyde level (p<0.05), which was correlated with increased inflammatory infiltration in cecal tissue of these groups. Conclusion: Pineapple crude extract inhibited sporulation and decreased the chance of E. tenella infection, but may be toxic by inducing cecal tissue inflammation.